2024
DOI: 10.1007/s41999-024-00959-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific comparisons in the rate of force development of toe pressure strength and its association with the timed up and go test

Taishiro Kamasaki,
Hiroshi Otao,
Shinichi Tanaka
et al.

Abstract: It has recently been recommended that Rate of Force Development (RFD) be evaluated in addition to maximal muscle strength. There are no studies on RFD of toe pressure strength, and its importance in older adults and the extent to which it is associated with aging needs to be clari ed. This study purpose was to examine the association between the RFD of toe pressure strength and Timed Up and Go Test (TUG) in an age-speci c study. MethodsThis study is a cross-sectional study. Participants in the study included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Additionally, Kamasaki et. al 2024 [45] reported a higher RFD among younger adults compared to older adults, which is consistent with the findings of this study, where the RFD was ~15N/s higher among younger adults. Although Kamaski et al did not report any sex-based differences, our study showed that males had 21N/s higher RFD than females.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, Kamasaki et. al 2024 [45] reported a higher RFD among younger adults compared to older adults, which is consistent with the findings of this study, where the RFD was ~15N/s higher among younger adults. Although Kamaski et al did not report any sex-based differences, our study showed that males had 21N/s higher RFD than females.…”
Section: Discussionsupporting
confidence: 92%
“…Kamasaki et. al 2024 and Sarikaya et al 2022 [45,46] reported a strong association of RFD in the great toe with better functional mobility and balance outcomes. Additionally, Kamasaki et.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation